Manipulating azobenzene photoisomerization through strong light–molecule coupling. Issue 1 (December 2018) - Fregoni, J.; Granucci, G.; Coccia, E.; Persico, M.; Corni, S.
Abstract The formation of hybrid light–molecule states (polaritons) offers a new strategy to manipulate the photochemistry of molecules. To fully exploit its potential, one needs to build a toolbox of polaritonic phenomenologies that supplement those of standard photochemistry. By means of a state-of-the-art computational photochemistry approach extended to the strong-coupling regime, here we disclose various mechanisms peculiar of polaritonic chemistry: coherent population oscillations between polaritons, quenching by trapping in dead-end polaritonic states and the alteration of the photochemical reaction pathway and quantum yields. We focus on azobenzene photoisomerization, that encompasses the essential features of complex photochemical reactions such as the presence of conical intersections and reaction coordinates involving multiple internal modes. In the strong coupling regime, a polaritonic conical intersection arises and we characterize its role in the photochemical process. Our chemically detailed simulations provide a framework to rationalize how the strong coupling impacts the photochemistry of realistic molecules. Manipulation of the photochemistry of molecules is traditionally achieved through synthetic chemical modifications. Here the authors use computational photochemistry to show how to control azobenzene photoisomerization through hybrid light–molecule states (polaritons).